Pada Suatu Drama: Studi Seni Pagelaran dalam Wacana Pergerakan - Rio Heykhal Belvage (Universitas Gadjah Mada, 2016)
A stage performance is not only a play, it has also become a medium to state somethingelse. It is possible that through the performance presented, the dynamics of life could bean inspiration for the creator to produce certain stories; constructing new reality. Everysingle scene seems unrelated at fi rst, but then combined to a story containing values.It can be social critique, politic strategy, entertainment, or money machine. Regardingthe context, this article is meant to be a critical refl ection to a particular play in TamanBudaya Yogyakarta (TBY). Here the writer is willing to share about spectator’s worldand a play performance carrying women movement issue; a stage imagined to be arefl ection of daily life, yet live so close to appreciations and full of paradoxes.